2008
DOI: 10.1016/j.virol.2008.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Potato virus A genome-linked protein VPg is an intrinsically disordered molten globule-like protein with a hydrophobic core

Abstract: Genome-linked protein VPg of Potato virus A (PVA; genus Potyvirus) has essential functions in all critical steps of PVA infection, i.e. replication, movement, and virulence. Structural features of the recombinant PVA VPg were investigated with the aim to create an outline for structure-function relationships. Circular dichroism data of PVA VPg revealed a distinct near-UV spectrum indicating that the environment around its aromatic residues is structured but rather flexible, and a far-UV spectrum that was chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
65
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 58 publications
5
65
0
Order By: Relevance
“…Disorder, however, is not a homogeneous state but comes in different structural flavors, ranging from random coil through premolten globule to a rather compact structural state denoted as molten globule (10,51). The native structure of PVA VPg is a partially disordered molten globule-like type (39,40). Our previous observations with circular dichroism (CD) spectroscopy, ANS (1-anilo-8-naphthalene sulfonate) binding, and disorder prediction are all consistent with this.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Disorder, however, is not a homogeneous state but comes in different structural flavors, ranging from random coil through premolten globule to a rather compact structural state denoted as molten globule (10,51). The native structure of PVA VPg is a partially disordered molten globule-like type (39,40). Our previous observations with circular dichroism (CD) spectroscopy, ANS (1-anilo-8-naphthalene sulfonate) binding, and disorder prediction are all consistent with this.…”
supporting
confidence: 66%
“…However, several recent studies have shown the intrinsic structural disorder of these proteins. The resulting structural flexibility has been proposed to enable VPg to carry out the variety of functions (16,20,40,44). The N terminus, NTP-binding region, and a short segment in the middle of the protein were speculated to be part of a natively unstructured stretch of amino acids, which may allow these regions to be multifunctional and structurally flexible and thereby facilitate participation of VPg in various interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of this Tyr residue with other amino acids abolishes infectivity of both viruses (Murphy et al, 1996;Germundsson et al, 2007). The intrinsically disordered structure of VPg (Grzela et al, 2008;Rantalainen et al, 2008) provides flexibility for many types of interactions with viral and host proteins (Hong et al, 1995;Li et al, 1997;Wittmann et al, 1997;Schaad et al, 2000;Guo et al, 2001;Dunoyer et al, 2004;Lé onard et al, 2004;Thivierge et al, 2008). Interactions between eIF4E or eIF(iso)4E (Wittmann et al, 1997;Schaad et al, 2000;Robaglia and Caranta, 2006) and VPg or NIa are important for virus infectivity (Lé onard et al, 2000;Robaglia and Caranta, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For Potato virus A (PVA), Potato virus Y, Lettuce mosaic virus, SeMV and RYMV an unfolded/disordered structure of VPg has been described previously (Grzela et al, 2008;Hébrard et al, 2009;Rantalainen et al, 2008;Satheshkumar et al, 2005). VPg proteins lack a unique 3D-structure and exist as a dynamic ensemble of conformations.…”
Section: Introductionmentioning
confidence: 99%